In vitro rumen fermentation characteristics due to Acanthopora muscoides (L.) Bory supplementation - Hidayah Nur; Sofia Firda Nasywa; Kustantinah; Astuti Andriyani; Hanim Chusnul; Noviandi Cuk Tri (BIO Web of Conferences)
In this study, a red macroalgae species, Acanthopora muscoides (L.) Bory was processed as a supplement Pennisetum purpureum cv. Gama Umami was used to evaluate their in vitro ruminant methane characteristics. This parameter will give us insight into the fermentation product from the feed degradation process condition in the rumen. A complete randomized block design with four treatments and four replications was used, with a time of rumen fluid collection as a block. The treatments consisted of control (only Pennisetum purpureum cv. Gama Umami as a basal diet) and supplementation Acanthopora muscoides (L.) Bory at 2.5, 5.0, and 7.5% organic matter (OM). The result showed that supplementing Acanthopora muscoides (L.) Bory up to 7.5.0% OM on Pennisetum purpureum cv. Gama Umami increased (P<0.01) total volatile fatty acid (VFA) production, propionate proportion, and microbial protein synthesis. Those treatments decreased (P<0.01) the proportion of acetate, butyrate, and acetate propionate ratio without disturbing pH value and NH3 concentration. The conclusion was Pennisetum purpureum cv. Gama Umami supplemented with Acanthopora muscoides (L.) Bory 7.5% OM is the best treatment in this study to increase rumen fermentation characteristics.